Detection of novel Betapapillomaviruses and Gammapapillomaviruses in eyebrow hair follicles using a singletube ‘hanging droplet’ PCR assay with modified pan-PV CODEHOP primers - Chouhy, Diego (2018)
A modified pan-PV consensus-degenerate hybrid oligonucleotide primer (CODEHOP) PCR was developed for generic and sensitive detection of a broad-spectrum of human papillomaviruses (HPVs) infecting the cutaneous epithelium. To test the analytical sensitivity of the assay we examined 149 eyebrow hair follicle specimens from immunocompetent male patients. HPV DNA was detected in 60% (89/149) of analysed eyebrow samples with a total of 48 different HPV sequences, representing 21 previously described HPVs and 27 putative novel HPV types. Evidence for ten novel HPV subtypes and seven viral variants, clustering to three out of five genera containing cutaneous HPVs, was also obtained. Thus, we have shown that the modified pan-PV CODEHOP PCR assay is able to identify multiple HPV types, even from different genera, in the same clinical sample. Overall, these results demonstrate that the pan-PV CODEHOP PCR is an excellent tool for screening and identification of novel cutaneous HPVs, even in samples with low viral loads.